PERANAN ETIKA, PEMERIKSAAN, DAN DENDA PAJAK UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Cahyonowati, Nur; Ratmono, Dwi; Faisal, Faisal (UI Scholars Hub, 2012)
This study aims to examine the determinants of compliance of Indonesian tax payers i.e. tax audit, fine and ethical variables. This study proposes a hypothesis that tax compliance is not only affected by deterrence factors such as tax audit and tax fine but also affected by the behavioral aspect of tax payers i.e. their ethics. The effects of tax audit and tax fine on tax compliance depend on ethical standard. This study designs experiment of 2x2 between subjects to examine the hypotheses. The participants of this experimental study are 40 tax payers in Semarang City. The results of this study suggest that there is an interaction between tax fine and ethics variables that affect tax compliance. However, there is no an empirical evidence of an interaction between ethics and tax audit that affect the level of tax compliance.